Teenagers Shopping Practices - Dayala, Sana Anis (Nurture, 2012)
The purpose of the research study was to know about the teenagers shopping practices related to their clothing. The research was conducted in the Gulshan town of Karachi through a convenient sample of 150 (75 boys and 75 girls) teenagers. Several aspects of teenagers (boys and girls) shopping were examined and compared: they enjoy shopping or not, factors affecting their shopping, factors they consider while buying, whom they shop with, what are their views about shopping of the teenagers and from where they prefer to shop? The results revealed no difference between boys and girls; they both are very keen for their personal shopping and are affected by fashion and media. They need opportunity to shop for themselves according their own choice. In view of other researches it is concluded that Teenagers are the fastest growing population and they must be given the opportunity to shop for themselves according to their own choice.